(untitled) (International Journal of Life Sciences Biotechnology and Pharma Sciences, 2024)
For several decades pharmacist have been aware of the need to protect their products against microbial contamination but it is only during the last one or perhaps two decades the serious thought of has been applied to the science of preservation. Preservatives are commonly used as additives in pharmaceutical products, food and cosmetics. Some of the liquid preparations are susceptible to microbial contamination because of the nature of ingredients present in it. Such preparations are protected by preservatives which avoids degradation and alternation of the product. A preservative is a natural or synthetic chemical added to various products which helps to prevent microbial decomposition. Present article deals with the study of ideal properties, classification, and mechanism of action, pharmaceuticals applications and its impacts on health of various preservatives used in pharmaceuticals.